Socioeconomic risk factors and age-related macular degeneration in the UK Biobank study. Issue 1 (23rd February 2021) - Yip, Jennifer Lai Yee; Muthy, Zaynah; Peto, Tunde; Lotery, Andrew; Foster, Paul J; Patel, Praveen
Abstract : Objective: There is contrasting evidence on the relationship between socioeconomic status (SES) and age-related macular degeneration (AMD), the most common cause of visual impairment (VI) in developed countries. This study examines the relationship between SES, cardiovascular risk factors and self-reported AMD. Methods and analysis: Over 500000 people participated in the UK Biobank study from 2006 to 2019, with sociodemographic data and clinical measurements collected using standardised procedures. Visual acuity was measured in 117907 participants with VI defined as LogMAR ≤0.3. We used logistic regression to examine the cross-sectional associations between SES and self-reported AMD. Results: Self-reported AMD was available for 133339 participants aged 50 and older. People reporting AMD had higher academic qualifications, lower income, were unable to work due to disability, have higher BMI, diabetes and vascular heart disease after adjusting for age and sex. In a multivariable analysis, higher income was protective of AMD and economic inactivity due to disability increased the odds of AMD (2.02, 95% CI 1.13 to 3.61). Both associations were independent of cardiovascular factors, but was no longer significant after adjusting for VI. Conclusions: The association between education, employment and household income with AMD was independent of cardiovascular risk factors.